A LITERATURE SURVEY ON CLIMATE FINANCE, GREEN FINANCE AND ENERGY FINANCE CONSIDERING THE IMPACT ON ECONOMIC GROWTH AND SUSTAINABLE DEVELOPMENT - BIRAU RAMONA; POPESCU VIRGIL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The main aim of this research study is to provide a literature survey on climate finance, green finance and energy finance in the context of impact on economic growth and sustainable development. The green finance policies play a significant role in achieving sustainable economic development, social responsibility and advancing environmental technologies. The recent advances in terms of green technologies innovation contribute to reducing the damage caused by severe climate change and aggravated pollution that affects the global economy. Moreover, considering the climatic disturbances of recent past, renewable energy finance represents an important challenge for achieving sustainable economic growth. Extreme climate changes and environmental degradation are key aspects that must be managed effectively by policymakers globally.